Long-term quality of VKA treatment and clinical outcome after extreme overanticoagulation in 14,777 AF and VTE patients - Kooistra, Hilde A. M.; Veeger, Nic J. G. M.; Khorsand, Nakisa; Kluin-Nelemans, Hanneke C.; Meijer, Karina; Piersma-Wichers, Margriet (Thrombosis and Haemostasis, 2015)
Vitamin K antagonists (VKA) are widely used in atrial fibrillation and venous thromboembolism (VTE). Their efficacy and safety depend on individual time in the therapeutic range (iTTR). Due to the variable dose-response relationship within patients, also patients with initially stable VKA treatment may develop extreme overanticoagulation (EO). EO is associated with an immediate bleeding risk, but it is unknown whether VKA treatment will subsequently restabilise. We evaluated long-term quality of VKA treatment and clinical outcome after EO. EO was defined as international normalized ratio (INR) ≥ 8.0 and/or unscheduled vitamin K supplementation. We included a consecutive cohort of initially stable atrial fibrillation and venous thromboembolism patients. In EO patients, the 90 days pre- and post-period were compared. In addition, patients with EO were compared with patients without EO using a matched 1:2 cohort. Of 14,777 initially stable patients, 800 patients developed EO. The pre-period was characterised by frequent overanticoagulation, and half of EO patients had an inadequate iTTR (< 65 %). After EO, underanticoagulation became more prevalent. Although the mean time between INR-measurements decreased from 18.6 to 13.2 days, after EO inadequate iTTR became more frequent (62 %), p-value < 0.001. A 2.3 times (95 % confidence interval [CI] 2.0–2.5) higher risk for iTTR< 65 % after EO, was accompanied by increased risk of bleeding (hazard ratio [HR] 2.1;CI 1.4–3.2), VKA-related death 17.0 (HR 17.0;CI 2.1–138) and thrombosis (HR 5.7;CI 1.5–22.2), compared to the 1600 controls. In conclusion, patients continuing VKA after EO have long-lasting inferior quality of VKA treatment despite intensified INR-monitoring, and an increased risk of bleeding, thrombosis and VKA-related death.Note: There have been no previous presentations, reports or publications of the complete data that appear in the article. Parts of the data in this article have been presented as a poster at the American Society of Hematology (ASH) congress 2013, New Orleans, United States.
Keywords: Overanticoagulation; vitamin K antagonists; iTTR; clinical outcome